Mastering™ Network Security, Second Edition - Brenton, Chris; Hunt, Cameron (Sybex, 2002)
The Technology You Need is Out There. The Expertise You Need is in Here. Expertise is what makes hackers effective. It's what will make you effective, too, as you fight to keep them at bay. Mastering Network Security has been fully updated to reflect the latest developments in security technology, but it does much more than bring you up to date. More importantly, it gives you a comprehensive understanding of the threats to your organization's network and teaches you a systematic approach in which you make optimal use of the technologies available to you. Coverage includes: Understanding security from a topological perspective Configuring Cisco router security features Selecting and configuring a firewall Configuring Cisco's PIX firewall Configuring an intrusion detection system Providing data redundancy Configuring a Virtual Private Network Securing your wireless network Implementing authentication and encryption solutions Recognizing hacker attacks Detecting and eradicating viruses Getting up-to-date security information Locking down Windows NT/2000/XP servers Securing UNIX, Linux, and FreBSD systems